PENDAYAGUNAAN LIMBAH INDUSTRI MIE SO’ON SEBAGAI MEDIA BUDIDAYA JAMUR, UPAYA PEMBERDAYAAN EKONOMI PEDESAAN DI KECAMATAN TULUNG, KABUPATEN KLATEN - Achmad Fatchul Aziez; Dwi Susilo Utami; Eko Hartoyo (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah Provinsi Jawa Tengah, 2010)
Daleman, Tulung, Klaten represent the industrial sentra of noodles so'on which is potential enough. industrial activity of making of noodles so'on by using raw material of bar of sugar palm will yield the waste which is quite a lot so that will bother the environment because yielding cyanide, as a result environment become malodorous and dirty.Target of this research is 1. Technological development of industrial the settlement of disposal alternative noodles so'on as media of mushroom conducting 2. Adding knowledge and skilled local society in the case of industrial the settlement of disposal of noodles so'on in mushroom conducting 3. Adding new employment to local society.The research applied factorial design arranged in Randomized Completely Block Design (RCBD), consisted of two factors and four replications. The first factor, kinds of mushroom (J) consisted of two levels (J1= Oyster mushroom and J2=ear mushroom). The second factor, the comparison of condisioner materials (grit : calcite : corn flour) (M), consisted of four levels. M1= 1:1:1 (15 kg grit : 2 kg calcity : 5 kg corn flour), M2 = 1:2:1 (30 kg bekatul : 4 kg calcity : 5 kg corn flour), M3 = 2:1:1 ( 30 kg grit : 2 kg calcity : 5 kg corn flour) and M4= 1:1:2 ( 15 kg grit : 2 kg calcity : 10 kg corn flour) The research has been done at Laboratory of Agriculture Faculty of Tunas Pembangunan University and Daleman, Tulung, Klaten from May until August 2009 Data analysis use the analysis variance and treatment which significant done a test continue by using Duncan Multiple Range Test level 5%. Parameter perceived to cover the : early growth of mycelium, height of stipe mushroom, diametre of stipe mushroom, number of stipe mushroom, total fresh weight of stipe mushroom, number of harvesting and protein content. The research concluded that : Kind of mushroom was very significant to the height of stipe mushroom, diameter of stipe mushroom, number of stipe mushroom, total fresh weight of stipe mushroom and number of harvesting, but was not significant to the early growth of mycelium. The comparison of condisioner materials was significant to the height of stipe mushroom, diameter of stipe mushroom, and number of harvesting, but was not significant to the early growth of mycelium, number of stipe mushroom, and total fresh weight of mushroom. Interaction between kinds of mushroom and comparison of condisioner materials was significant to the diameter of stipe mushroom and number of harvesting, but was not significant to the other parameters. The highest total fresh weight of mushroom ( 183,59 g/media), was found at the treatment of interaction oyster mushroom and 15 kg grit + 2 kg calcity + 5 kg corn flour. The lowest total fresh weight of mushroom ( 51,25 g/media) was found at the treatment of interaction ear mushroom and 15 kg grit + 2 kg calcity + 5 kg corn flour.